Distribusi komponen karkas sapi Brahman Cross (BX) hasil penggemukan pada umur pemotongan yang berbeda - Muhamad Iqbal Zajulie; Moch Nasich; Trinil Susilawati; Kuswati Kuswati (Faculty of Animal Science, Universitas Brawijaya, 2015)
The aim of this study was to determine the distribution of beef carcass component from Brahman Cross cattle at different slaughtered age. The number of cattle was 99 head (49 steers and 50 heifers), the body weight 350 - 500 kg and age ranged PI0 - PI2 classess. The cattle were raised in PT. Widodo Makmur Perkasa and then slaughtered at slaughter house in Cianjur District, West Java. Accidental sampling method was applied to the research. A direct observation was done to obtain information about age, sex, body weight and carcass weight and its part (meat, bone and fat). The data were analyzed using independent t-test, correlation and linear regresion. The result showed that the average slaughtered weight and carcas weight of Brahman Cross heifers was higher than that of Brahman Cross steers at PI0 sex-class (P<0.05). However, the dressing percentage was relatively similar (P>0.05). Average meat percentage of heifers and steers was also relatively similar (73.39% : 73.65%). Average bone percentage of steers was higher than that of heifers (14.82% : 14.33 %). Whereas, average fat percentage of heifers was higher than that of steers (11.00% : 10.21%). The research concluded that steers of Brahman Cross cattle at all age-classess had better distribution of carcass component than heifers in the same age-classess. Steers of Brahman Cross cattle at PI2 slaughtered age-class had an optimal distribution of carcass components. Keyword: Brahman Cross, slaughtered age, sex-class, distribution, carcas component.